Drama DRAMA MUSIKAL: PETER AND THE WOL Karya Sergie Prokofiev,Op.67, Sebagai Bentuk Orchestrasi Dongeng: Pendahuluan - Tatang Rusmana (Jurusan Sendratasik FBS Unesa, 2022)
Peter And The Wolf (A Symphonic tale for Children) by Sergei Prokofiev, Op. 67, written by Prokofiev in 1936. The performance of this tale is like a monologue drama. It is rare to find a tale performance or a monologue drama that is composed with music in an ensemble. The narrator tells a children's story, while the orchestra illustrates it using different instruments to play a